Fatal bone marrow embolism in a patient with sickle cell beta + thalassaemia. Issue 9 (September 1996) - Zaidi, Y; Sivakumaran, M; Graham, C; Hutchinson, R M
Abstract : Sickle cell beta + thalassaemia is regarded as the mildest of the sickle cell haemoglobinopathy syndromes with a benign natural course. In contrast to sickle cell disease, severe life threatening complications are not usually associated with this genotype. A case of a 30 year old West Indian man who, previously asymptomatic for 10 years, sustained a fatal pulmonary bone marrow embolism, is reported. This case report illustrates that serious, even fatal, complications may occur in patients with this 'benign' condition and bone marrow embolism should be included in the differential diagnosis of acute crisis in these patients.